Mutational spectrum of the oral-facial-digital type I syndrome: A study on a large collection of patients - ELÇİOĞLU, HURİYE NURSEL (Wiley-Liss Inc., 2008)
Oral-facial-digital type I (OFDI) syndrome is a male-lethal X-linked dominant developmental disorder belonging to the heterogeneous group of oral-facial-digital syndromes (OFDS). OFDI is characterized by malformations of the face, oral cavity, and digits. Central nervous system (CNS) abnormalities and cystic kidney disease can also be part of this condition. This rare genetic disorder is due to mutations in the OFD1 gene that encodes a centrosome/basal body protein necessary for primary cilium assembly and for left-right axis determination, thus ascribing OFDI to the growing number of disorders associated to ciliary dysfunction. We now report a mutation analysis study in a cohort of 100 unrelated affected individuals collected worldwide. Putative disease-causing mutations were identified in 81 patients (81%). We describe 67 different mutations, 64 of which represent novel mutations, including 36 frameshift, nine missense, 11 splice-site, and 11 nonsense mutations. Most of them concentrate in exons 3, 8, 9, 12, 13, and 16, suggesting that these exons may represent mutational hotspots. Phenotypic characterization of the patients provided a better definition of the clinical features of OFDI syndrome. Our results indicate that renal cystic disease is present in 60% of cases >18 years of age. Genotype-phenotype correlation did not reveal significant associations apart for the high-arched/cleft palate most frequently associated to missense and splice-site mutations. Our results contribute to further expand our knowledge on the molecular basis of OFDI syndrome. © 2008 Wiley-Liss, Inc.
Keywords: Mutation analysis; OFD1; OFDI; Primary ciliary dysfunction; X-linked dominant male lethal